Implementasi Prinsip Hermeneutik dalam Pendidikan Anak Usia Dini: Dari Analisis Cerita ke Arah Pembentukan Karakter Anak (Pusat Riset dan Inovasi Nasional, 2026)
Early Childhood Education (ECE) is an important stage in shaping a child's personality and character. At this point, the story serves as the primary tool for conveying principles, ethics, and the meaning of life. However, the process of interpreting stories often overlooks cognitive aspects and lacks focus on children's character development. The purpose of this article is to study how hermeneutic principles are used in early childhood education, with a particular emphasis on how stories function as a tool for shaping children's character. The hermeneutic method allows educators to interpret stories contextually, dialogically, and reflectively. This allows children to understand and internalize the principles contained in the story. This research utilizes a qualitative-descriptive literature study on hermeneutic literature, character education, and early childhood pedagogy. The results indicate that hermeneutics, employing principles such as the hermeneutic circle, dialog of meaning, and contextualization of stories, significantly enhances honesty, empathy, responsibility, and religious attitudes in early childhood. Thus, hermeneutics is not only relevant in adult text research, but also effective as a pedagogical method in teaching early childhood.